2007
DOI: 10.1111/j.1872-034x.2007.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased TFF1 trefoil protein expression in Opisthorchis viverrini‐associated cholangiocarcinoma is important for invasive promotion

Abstract: TFF1 showed co-expression with MUC5AC in CCA tissues and invasive stimulating activity in vitro. These results may indicate a role for TFF1 in promoting tumor invasion in CCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Tissue specimens were kept as paraffin-embedded formaldehyde fixed. The CCA cell lines, KKU-100 and KKU-M213, were established in the Department of Pathology, Faculty of Medicine, Khon Kaen University, Thailand (Sripa et al 2005;Thuwajit et al 2007). KKU-100 and KKU-M213 cells were developed from poorly and well-differentiated CCA tissues, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tissue specimens were kept as paraffin-embedded formaldehyde fixed. The CCA cell lines, KKU-100 and KKU-M213, were established in the Department of Pathology, Faculty of Medicine, Khon Kaen University, Thailand (Sripa et al 2005;Thuwajit et al 2007). KKU-100 and KKU-M213 cells were developed from poorly and well-differentiated CCA tissues, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study showed that TFF1 is not expressed in hepatocytes and minimally expressed in normal cholangiocytes (Sasaki et al 2003). However, a high expression of TFF1 has been reported in CCA cells (Thuwajit et al 2007). The in vitro studies have shown the stimulation of TFF1 on cell invasion in CCA (Thuwajit et al 2007) and breast cancer (Prest et al 2002).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…To evaluate the possible biological functions correlated to the metal binding ability of TFF1, we studied the effects of copper binding on the well-described motogenic activity of TFF1 [26,27]. To this aim, we used an inducible hyperexpressing clone of the gastric carcinoma cell line AGS (AGS-AC1) (Fig.…”
Section: Copper (Ii) Binding Affinitymentioning
confidence: 99%